Text recycling in health sciences research literature: a rhetorical perspective. Issue 1 (December 2017) - Moskovitz, Cary
Abstract The past few years have seen a steady rise in the number of health science journals using plagiarism detection software to screen submitted manuscripts. While there is widespread agreement about the need to guard against plagiarism and duplicate publication, the use of such tools has sparked debate about text recycling—the reuse of material from one's prior publications in a new manuscript. Many who have published on the topic consider all uses of text recycling anathema. Others argue that some uses of recycling are unavoidable and sometimes even beneficial for readers. Unfortunately, much of this discourse now merely repeats dogmatic assertions. I argue that progress can be made by acknowledging three points: First, citation standards for research writing in the health sciences will not mirror those of the humanities. Second, while it is impossible to draw a definitive line between appropriate and inappropriate uses of text recycling, some uses of the practice lie clearly on the legitimate side. Third, the needs of editors for information regarding recycled text are different from those of readers. Ultimately, calls for rewording and citation as alternatives or fixes for text recycling are unlikely to prove satisfactory to either readers or editors. A response to this article can be found using the following link:http://researchintegrityjournal.biomedcentral.com/articles/10.1186/s41073-017-0026-y .